2007
DOI: 10.1007/s00441-007-0409-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperalgesia in response to traumatic occlusion and GFAP expression in rat parabranchial nucleus: modulation with fluorocitrate

Abstract: We have examined, by immunocytochemical methods and nociceptive behavior assessment in rats, whether astrocytes in the parabrachial nucleus (PBN) are involved in the regulation of traumatic occlusion. The expression of glial fibrillary acidic protein (GFAP) in PBN of ipsilateral and contralateral sides was up-regulated 4 h after occlusal changes in molars, reached peak levels at 24 h, and was then gradually down-regulated. PBN astrocytes activated by traumatic occlusion were found to have enlarged cell bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This direct filling method cannot be quantified easily due to operating inside the mouth and usually destroys the pulpal tissues of rats, strongly stimulating pulpal nerve fibres. Pre‐made onlays, pre‐made crowns and orthodontic bands were cemented to one or more teeth to raise the bite . These methods are more easily and precisely quantified because the aforementioned appliances can be measured at multiple points out of the mouth before being cemented.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This direct filling method cannot be quantified easily due to operating inside the mouth and usually destroys the pulpal tissues of rats, strongly stimulating pulpal nerve fibres. Pre‐made onlays, pre‐made crowns and orthodontic bands were cemented to one or more teeth to raise the bite . These methods are more easily and precisely quantified because the aforementioned appliances can be measured at multiple points out of the mouth before being cemented.…”
Section: Animal Studiesmentioning
confidence: 99%
“… used nociceptive behaviour assessment to examine a rat model having an orthodontic square wire bonded onto the occlusal surface of the first upper molar to raise it approximately 1 mm unilaterally. The rats were assessed for nociceptive behaviour at 1, 2, 4, 8, 24 and 72 h after bite‐raising, and a bilateral mechanical hyperalgesia response to mechanical stimulation was noted at 8, 24 and 72 h . Another rat study revealed mechanical hyperalgesia of the skin in the temporalis and masseter muscles after 1‐mm bite‐raising .…”
Section: Animal Studiesmentioning
confidence: 99%
“…The results suggested that the GFAP‐immunoreactive astrocytes in PBN within the bridge of Varolius were activated by traumatic occlusion and that they were involved in the transmission and modulation of nociceptive information in the CNS. However, although astrocytes in PBN were thus probably involved in causing post‐occlusal hyperalgesia, the researchers had not been able to exclude that astrocytes at other locations also contribute to this effect .…”
Section: Resultsmentioning
confidence: 95%
“…Together, these substances regulate the conduction of noxious stimuli . Some researchers examined by immunocytochemical methods and nociceptive behaviour assessment in rats whether astrocytes in the parabrachial nucleus (PBN) were involved in the regulation of traumatic occlusion . The expression of GFAP in PBN of ipsilateral and contralateral sides was up‐regulated 4 h after occlusal changes in molars, reached peak levels at 24 h and was then gradually down‐regulated .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation